Effect of Phosphoglucosamine Mutase on Biofilm Formation and Antimicrobial Susceptibilities in M. smegmatis glmM Gene Knockdown Strain - Kang, Jian (Public Library of Science, 2013)
UDP-N-acetylglucosamine (UDP-GlcNAc) is a direct glycosyl donor of linker unit (L-Rhamnose-D-GlcNAc) and an essential precursor of peptidoglycan in mycobacteria. Phosphoglucosamine mutase (GlmM) is involved in the formation of glucosamine-1-phosphate from glucosamine-6-phosphate, the second step in UDP-GlcNAc biosynthetic pathway. We have demonstrated that GlmM protein is essential for the growth of M. smegmatis. To facilitate the analysis of the GlmM protein function in mycobacteria, a tetracycline inducible M. smegmatis glmM gene knockdown strain was constructed by using an antisense RNA technology. After induction with 20 ng/ml tetracycline, the expression of GlmM protein in glmM gene knockdown strain was significantly decreased, resulting in a decline of cell growth. The morphological changes of glmM gene knockdown strain induced with 20 ng/ml tetracycline have been observed by scanning electron microscope and transmission electron microscope. Furthermore, insufficient GlmM protein reduced the biofilm formation and increased the sensitivity to isoniazid and ethambutol in M. smegmatis, indicating that GlmM protein had effect on the biofilm formation and the senstivity to some anti-tuberculosis drugs targeting the cell wall. These results provide a new insight on GlmM functions in mycobacteria, suggesting that GlmM could be a potential target for development of new anti-tuberculosis drug.